PsycEXTRA Dataset 2008
DOI: 10.1037/e599972012-001
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Policies and Strategic Communication in Iran: The Value of Public Opinion Research in Decisionmaking

Abstract: World Bank Working Papers are published to communicate the results of the Bank's work to the development community with the least possible delay. The manuscript of this paper therefore has not been prepared in accordance with the procedures appropriate to formally-edited texts. Some sources cited in this paper may be informal documents that are not readily available. The findings, interpretations, and conclusions expressed herein are those of the author(s) and do not necessarily reflect the views of the Intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 0 publications
2
7
1
Order By: Relevance
“…5. Opinion about current environmental legislations/ laws (Calabrese et al, 2008). A total of four statements were used targeting the adequacy of current laws for preventing environmental degradation, level of enforcing these laws, and whether they could cover the ordinary people or whether there is a need to pass more laws to protect the environment.…”
Section: Data Collection Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…5. Opinion about current environmental legislations/ laws (Calabrese et al, 2008). A total of four statements were used targeting the adequacy of current laws for preventing environmental degradation, level of enforcing these laws, and whether they could cover the ordinary people or whether there is a need to pass more laws to protect the environment.…”
Section: Data Collection Methodsmentioning
confidence: 99%
“…Worry (concern) about environmental problems that arise due to lack of adoption of integrated environmental management (IEM) systems. A Worry scale composed of eight statements, each concerned with one environmental problem, was applied (Calabrese et al, 2008). The scale targeted worries about reuse of treated wastewater in agriculture and aquaculture, reuse of composted sludge in agriculture, contamination of public water bodies and fisheries, odor emissions, densification and network overloads, sewer overflows in rainy seasons, and the severe adverse health problems.…”
Section: Data Collection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown in other studies in Iran that considering all stakeholders' interests can result in achieving both local community development and conservation goals (Zarandian et al, 2017). It is also argued that DOE has been more successful in solving environmental issues when involved in collaboration with other government bodies (Calabrese et al, 2008). In general, to develop a comprehensive development plan to bring a balance between community development and environmental conservation around protected areas, there is a need for all the stakeholders, such as the different government bodies to work together.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found that in Iran, environmental issues are not usually considered as significant as other socioeconomic problems (Calabrese, Kalantari, Santucci, & Stanghellini, 2008;Kolahi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%